Development of multiple interactions mixed matrix membrane chromatography using lewatit MP500 anion resin and lewatit CNP 105 cation resin for whey protein fractionation - Shiew, Chan Fong (2013)
The conventional method to purify protein is by using packed bed column chromatography. However, this method had several limitations such as high pressure drop and limited flow rate operation. Membrane chromatography can be used to overcome the limitation of packed column but the preparation of adsorptive membrane requires harsh chemical modifications. Mixed matrix membrane (MMM) preparation concept can be used as an alternative route to prepare membrane chromatography by physical blending of adsorptive resin with membrane polymer solution. In the current research, multiple interactions MMM chromatography was developed for whey protein fractionation using 7.5 wt% CNP105 cation resin and 42.5 wt% MP500 anion resin relative to base polymer content. The resins were blend at different composition in EVAL and cellulose base polymer matrix. Based on HPLC and SDS-PAGE analysis, both acidic and basic whey proteins were bound to the multiple interactions MMM in single run of whey batch fractionation. The binding capacity for major acidic whey proteins using EVAL based MMM are 4.255 mg BSA bound/ g MMM, 60.887 mg α-Lac bound/ g MMM and 231.788 mg β-Lac/ g MMM. For CA based MMM, the binding capacity are 2.970 mg BSA bound/ g MMM, 42.392 mg α-Lac bound/ g MMM and 179.817 mg β-Lac/ g MMM.